ANALISIS PENERAPAN ETIKA BISNIS PADA UKM PENGOLAH HASIL LAUT DI KELURAHAN SUKOLILO BARU KECAMATAN BULAK KOTA SURABAYA - Kusuma, Yanda Bara; Fatmawati, Rini (Jurnal Dinamika Administrasi Bisnis, 2019)
Ethics is an important issue in business activities at the moment. This study is to find out how the application of Business Ethics in Sea Products Processing SMEs in Sukolilo Baru Village, Bulak District, Surabaya, especially in UKM Toko Risma. The type of research used is qualitative research. The focus of this research is the application of the principles of business ethics carried out by SMEs in Seafood Processing in Sukolilo Baru Village, Bulak District, Surabaya. The results of the Toko Risma  research have considered and applied several business ethics principles. Starting from the principle of autonomy, honesty, justice, mutual benefit, and moral integrity. Toko Risma does not use preservatives, the product only lasts about one month and for coloring it usually uses cake coloring that is safe for consumption. Keywords: Business Ethics, UKM, Toko Risma